Penerapan kooperatif berbantuan media domino matematika dalam mingkatkan hasil belajar siswa kelas II SD Inpres 12/79 Amali riattang - Muh. Zulpadli Syam; Firdaus; Achmad Shabir (MACCA : Science-Edu Journal, 2026)
This study aims to describe student activities, teacher activities, and the improvement of mathematics learning outcomes through the application of a cooperative approach assisted by mathematical domino media for second-grade students of SD Inpres 12/79 Amali Riattang, Bone Regency. This study is a Classroom Action Research (CAR) with a qualitative approach implemented in two cycles, where each cycle consists of planning, implementation, observation, and reflection stages. The research subjects were 16 students. Data collection techniques were carried out through observation and learning outcome tests. The results showed that in the first cycle the learning activities were still in the sufficient category, with the percentage of student learning completion of 37.5%. In the second cycle, there was a significant increase where teacher and student activities were in the good category and learning completion increased to 75%. This increase indicates that the application of a cooperative approach assisted by mathematical domino media can increase student engagement in learning, foster cooperation, and help students understand mathematical concepts more easily and enjoyably. Thus, this approach is effective in improving elementary school students' mathematics learning outcomes.